School absenteeism as a predictor of functional gastrointestinal disorders in children - Tersteeg, Seth M.; Borowitz, Stephen M. (Frontiers in Pediatrics, 2024)
IntroductionChronic abdominal complaints are common in school-aged children. Most affected children do not have underlying organic diseases but suffer from functional gastrointestinal disorders. While many children with chronic abdominal complaints experience school problems, no prospective studies have examined if school absenteeism is more common among children suffering from functional as opposed to organic gastrointestinal disorders. The purpose of this study was to determine if there is an association between school absenteeism and functional gastrointestinal disorders in children presenting to a pediatric gastroenterology clinic with chronic gastrointestinal complaints.MethodsOver a single year, families of school-aged children presenting to a pediatric gastroenterology clinic with gastrointestinal complaints were asked how many days of school their child had missed in the previous month due to their symptoms. At least six months after their visit, each child's final diagnosis was established and categorized as a functional disorder or an organic disease. Differences between children suffering from each diagnosis type were compared using unpaired t-tests.ResultsChildren with functional gastrointestinal disorders were more likely to experience significant school absenteeism than children with gastrointestinal diseases. Missing more than three days of school in the month prior to their visit had a negative predictive value of 82% for a gastrointestinal disease and being homebound from school during the month prior to their visit had a negative predictive value of 88% for a gastrointestinal disease. As compared to children with functional disorders, those with organic diseases were more likely to have missed three or fewer days of school in the previous month (sensitivity = 93%) and to have attended any school in the previous month (sensitivity = 99%).DiscussionOur data suggest children with functional gastrointestinal disorders are more likely to experience significance school absenteeism than children suffering from organic diseases. We suspect this may be due to higher perceived levels of pain and symptom catastrophizing caused by the duration and character of the diagnostic process, as well as biopsychosocial characteristics of these children.